SHAPING THE CHILD'S WORLD: THE APPLICATION OF JEAN PIAGET'S THEORY OF COGNITIVE DEVELOPMENT IN EDUCATION - Hani Maftukha; Nasikhin; Fihris (ARIMA : Jurnal Sosial Dan Humaniora, 2025)
This article aims to analyze the application of Piaget's theory in education, identify the challenges of its implementation, and formulate effective strategies to optimize learning based on children's cognitive development. The research method used is a qualitative literature study with content analysis of theoretical sources such as books, journals, and related scientific articles. The results of the study indicate that the application of Piaget's theory emphasizes active learning and constructivism, where children learn through direct exploration. However, its implementation faces challenges such as differences in students' cognitive development levels, limited facilities and infrastructure, and a rigid curriculum, teachers who are less trained in the constructivist approach, as well as cultural and social factors. The proposed solutions include active learning through exploration, the use of concrete media, social interaction in learning, adjusting the curriculum to the developmental stage, teacher training on constructivism, and process-based evaluation. This article concludes that Piaget's theory remains relevant in modern education, as long as it is supported by flexible teaching methods and a stimulating learning environment. The implication is that educators need to adapt learning practices according to children's cognitive stages to encourage optimal intellectual development.